Farmer Scientist Forum: an approach to Market led Extension - K.D. Kokate; P.B. Kharde; S.S. Patil (Journal of Agricultural Extension Management, 2025)
The present day agriculture is defined by the key concept of stability, sustainability, diversification and commercialization. In the last decade, the agricultural situation in India has undergone a tremendous change in the light of liberalization and establishment of the World Trade Organization (WTO). India’s signing of the General Agreement on Tariffs and Trade (GATT) in 1994 and joining of WTO has put our agricultural sector into a framework of the global market. Low productivity of crops added to less remunerative market prices of agricultural commodities are the major causes of worry. Thus, agricultural enterprise is found to be not very profitable although a large majority is dependent on it. With the globalization of agriculture, major emphasis is laid on increasing the productivity of crops. During the last 50 years, major emphasis has been on Production led Extension